"Force Disguised as Reason": Law, Jurists, and Constituent Power in Boccaccio's Decameron. Issue 4 (1st July 2018) - Vespaziani, Alberto
Abstract : This Article presents the Decameron, by Giovanni Boccaccio, as a classic writing of universal literature that contains anticipations and fundamental innovations of the political categories of modernity: Contractualism, constituent power, constitutional deliberation, rhetoric, and the relation with Fortuna. The argument is developed in three parts: Initially, the legal and European dimension of the Decameron are summarized; then the discussion focuses on legal issues and institutional characters narrated in the novels; finally, the introduction of the work is analyzed, in which both the political-constitutional theme of the new beginning of the community and the collective archetype of the plague are interpreted as metaphors for the state of exception.